A Generalized Evaporation Model for Chinese Pans. Issue 19 (9th October 2018) - Wang, Kaiwen; Liu, Xiaomang; Li, Yuqi; Liu, Changming; Yang, Xiaohua
Abstract: Pan evaporation ( E pan ) measurements are used for gauging the atmospheric evaporative demand, and E pan observation networks were established and maintained for a long history. However, due to the replacement of D20 pans with 601B pans across China in 2000, E pan observation networks in China, which is the largest networks in East Asia, became discontinuous. Thus, it is important to develop a robust method to update and complement E pan of two Chinese pans. PenPan model is a robust model in E pan estimation, while the previous versions of PenPan are derived for a specific type of pan. This study developed a generalized model, that is, PenPan‐V3 model, to simulate E pan for Chinese pans. The PenPan‐V3 model simulated the irradiance of each part of pans; that is, pan water surface, pan rim, side wall and pan bottom, and the simulated E pan coincided with the observations of D20 and 601B pans. For D20 pans, aerodynamic component ( E pan, A ) and radiative component ( E pan, R ) of E pan were 60% and 40%, respectively. The contributions of pan water surface, inside and outside pan rim, side wall, and pan bottom to E pan, R were 23%, 38%, 26%, 6%, and 7%, respectively. For 601B pans, E pan, A and E pan, R were 42% and 58% of E pan, respectively. The contributions of pan water surface and inside and outside pan rim to E pan, R were 94%, 5% and 1%, respectively. The PenPan‐V3 model benefits establishing the long‐term continuous E pan networks in China, which can be used for evaluating the long‐term trends of atmospheric evaporative demand in East Asia. Key Points: A generalized pan evaporation model, PenPan‐V3, was built to simulate the monthly pan evaporation of two Chinese pans The PenPan‐V3 model simulates the irradiance of each part of a pan, that is, pan water surface, pan rim, side wall, and pan bottom The PenPan‐V3 model can be used to update and complement the long‐term evaporation networks of D20 and 601B pans in China